2016
DOI: 10.1108/bfj-10-2015-0389
|View full text |Cite
|
Sign up to set email alerts
|

Creating value chains: the role of relationship development

Abstract: Purpose -The purpose of this paper is to identify the key characteristics of business-to-business relationships in the early stages of the relationship that will influence the successful creation of value chains. Identification of these characteristics will provide a decision-making tool for continuing the effective development of the value chain process. Design/methodology/approach -Key characteristics necessary to develop strong relationships were identified from the literature. These characteristics will as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(66 citation statements)
references
References 67 publications
(97 reference statements)
3
61
0
2
Order By: Relevance
“…The main common feature of each group of respondents is the fact that all of them are participants at certain marketing channel. Even traditional purchasers play this role (compare Wagner et al., 2011; Hastings et al., 2016). However, the level of their desired marketing activity is quite different, and thus their degree of integration with offerors is different too.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main common feature of each group of respondents is the fact that all of them are participants at certain marketing channel. Even traditional purchasers play this role (compare Wagner et al., 2011; Hastings et al., 2016). However, the level of their desired marketing activity is quite different, and thus their degree of integration with offerors is different too.…”
Section: Resultsmentioning
confidence: 99%
“…Ethics is definitely the basis for building and strengthening good mutual relations over a long period of time. The relational dimension of intra-channel integration is also highlighted as vital (inter alia, Palmatier et al., 2015; Wagner et al., 2011; Hastings et al., 2016), which proves that the degree of integration between purchasers and offerors can be determined by analysing the character of the relationship between these two parties.…”
Section: Introductionmentioning
confidence: 99%
“…() introduced a conceptual framework for evaluating the market orientation of value chains in the food industry; see also Trienekens (). Roep and Wiskerke () have suggested that the agri‐food industry has been among the last to shift to a consumer‐focused market orientation, but studies are emerging that compare different value chains and evaluate potential success factors (Brinkmann et al ., ; Value Chain Management Centre, ; Macharia et al ., ; Trienekens and Wognum, ; Hastings et al ., ). This has included studies of agri‐food value chains sourced from New Zealand, including the research of Skallerud and Olsen (), Akhtar and Khan (), Trienekens et al .…”
Section: Agricultural Economics and Dynamic Capabilitiesmentioning
confidence: 97%
“…Thus, trust is the general relationship indicator (Meng, 2010), it is at the heart of a relationship (Kam and Lai, 2018). Trust is a relational feature important for collaboration (Hastings et al, 2016). It contributes to the collaboration tendency to enter and follow inter-firm relationships (Madhok, 2006).…”
Section: Organizational Performancementioning
confidence: 99%